Backup transcription factor binding sites protect human genes from mutations in the promoter. - Jay C Brown (PLoS ONE)
This study was designed to test the idea that the regulatory regions of human genes have evolved to be resistant to the effects of mutations in their primary function, the control of gene expression. It is proposed that the transcription factor/transcription factor binding site (TF/TFBS) pair having the greatest effect on control of a gene is the one with the highest abundance among the regulatory elements. Other pairs would have the same effect on gene expression and would predominate in the event of a mutation in the most abundant pair. It is expected that the overall regulatory design proposed here will be highly resistant to mutagenic change that would otherwise affect expression of the gene. The idea was tested beginning with a database of 42 human genes highly specific for expression in brain. For each gene, the five most abundant TF/TFBS pairs were identified and compared in their TFBS occupancy as measured by their ChIP-seq signal. A similar signal was observed and interpreted as evidence that the TF/TFBS pairs can substitute for one another. TF/TFBS pairs were also compared in their ability to substitute for one another in their effect on the level of gene expression. The study of brain specific genes was complemented with the same analysis performed with 31 human liver specific genes. Like the study of brain genes, the liver results supported the view that TF/TFBS pairs in liver specific genes can substitute for one another in the event of mutagenic damage. Finally, the TFBSs in the brain specific and liver specific gene populations were compared with each other with the goal of identifying any brain selective or liver selective TFBSs. Of the 89 TFBSs in the pooled population, 58 were found only in brain specific but not liver specific genes, 8 only in liver specific but not brain specific genes and 23 were found in both brain and liver specific genes. The results were interpreted to emphasize the large number of TFBS in brain specific genes.